Stochastic behavioral models for system level reliability analysis including non-normal and correlated process variation. (March 2021) - Taddiken, Maike; Hillebrand, Theodor; Peters-Drolshagen, Dagmar; Paul, Steffen
Abstract: The behavior of modern integrated circuits is altered by numerous effects such as process variation, voltage or temperature shifts and aging (PVTA). To evaluate the impact on system level, extensive simulations must be carried out on transistor-level which is not applicable for larger systems. This paper presents methods for the generation of stochastic behavioral models (SBMs) of circuit components to enable the reliability analysis of individual performances on system level. Different modeling approaches are presented, based on either Response Surface Models for parametric or Kernel Density Estimation for non-normal performance distributions. Additionally, an approach to incorporate the correlation between individual system components is analyzed. The SBMs are evaluated on analog example circuits consisting of several components. Highlights: Stochastic behavioral models for reliability analysis of integrated circuits Modeling approaches for parametric and non-normal distributions Considering correlation between subsystems Good accuracy and simulation speedup results